2010
DOI: 10.4315/0362-028x-73.7.1313
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Species Isolated from Retail Meats in Korea

Abstract: This study was conducted to determine the prevalence of Arcobacter species identified or isolated from retail meats in Korea. Multiplex PCR assays for the detection of Arcobacter species were performed for 360 chicken, 100 pork, and 106 beef samples. Arcobacter butzleri and Arcobacter cryaerophilus were detected in 18.9 and 3.3% of chicken samples, respectively. However, Arcobacter species were not found in any of the pork and beef samples. Biochemical testing of isolates selected after enrichment revealed 38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Although the Arcobacter contamination rates obtained in this study were consistent with those in previous reports (23,42), studies in the United States and Japan showed much lower rates than those reported herein (43,44). In contrast to molecular detection, bacterial culture for Arcobacter spp.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Although the Arcobacter contamination rates obtained in this study were consistent with those in previous reports (23,42), studies in the United States and Japan showed much lower rates than those reported herein (43,44). In contrast to molecular detection, bacterial culture for Arcobacter spp.…”
Section: Discussionsupporting
confidence: 89%
“…Bacterial culture is not practical for the rapid detection of Arcobacter species because of their slow growth in Campylobacter blood-free selective medium; therefore, conventional PCR, multiplex PCR, and enterobacterial repetitive intergenic consensus (ERIC)-PCR were used in previous studies for the rapid detection of Arcobacter spp. (23,35,36). In this study, five C. jejuni strains and one C. coli strain were detected as false positives by multiplex PCR described previously (26).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations